Costs and possible benefits of a two-tier infection control management strategy consisting of active screening for multidrug-resistant organisms and tailored control measures. Issue 2 (June 2016) - Mutters, N.T.; Günther, F.; Frank, U.; Mischnik, A.
Summary: Background: Multidrug-resistant organisms (MDROs) are an economic burden, and infection control (IC) measures are cost- and labour-intensive. A two-tier IC management strategy was developed, including active screening, in order to achieve effective use of limited resources. Briefly, high-risk patients were differentiated from other patients, distinguished according to type of MDRO, and IC measures were implemented accordingly. Aim: To evaluate costs and benefits of this IC management strategy. Methods: The study period comprised 2.5 years. All high-risk patients underwent microbiological screening. Gram-negative bacteria (GNB) were classified as multidrug-resistant (MDR) and extensively drug-resistant (XDR). Expenses consisted of costs for staff, materials, laboratory, increased workload and occupational costs. Findings: In total, 39, 551 patients were screened, accounting for 24.5% of all admissions. Of all screened patients, 7.8% ( N = 3, 104) were MDRO positive; these patients were mainly colonized with vancomycin-resistant enterococci (37.3%), followed by meticillin-resistant Staphylococcus aureus (30.3%) and MDR-GNB (28.3%). The median length of stay (LOS) for all patients was 10 days (interquartile range 3–20); LOS was twice as long in colonized patients ( P < 0.001). Screening costs totalled 255, 093.82€, IC measures cost 97, 701.36€, and opportunity costs were 599, 225.52€. The savings of this IC management strategy totalled 500, 941.84€. Possible transmissions by undetected carriers would have caused additional costs of 613, 648.90–4, 974, 939.26€ (i.e. approximately 600, 000–5 million €). Conclusion: Although the costs of a two-tier IC management strategy including active microbiological screening are not trivial, these data indicate that the approach is cost-effective when prevented transmissions are included in the cost estimate.